PO028 Time 2: a replication study of transient epileptic amnesia. (1st December 2017) - Baker, John; Savage, Sharon; Zeman, Adam
Abstract : Background: We described the first large cohort of patients with Transient Epileptic Amnesia (TEA) in 2007 (n=50). Smaller series of patients have recently been reported from France and Italy. Continuing referrals to our website (http://projects.exeter.ac.uk/time/) from around the world suggest that the condition remains underrecognised. Here we describe findings in British patients referred to our study since 2007. Methods: 66 patients were recruited using previously established diagnostic criteria. We assessed clinical features and performed neuropsychological evaluation, using our previous test battery. Results: TEA develops in later life (mean age of onset=60.5 years, mean age at presentation=64.8 years) and is more common in males (M:F=46:20). Attacks are typically infrequent (median 12/yr) and commonly occur on waking (61 of 66 cases). Duration of TEA episodes is variable, although the most commonly reported duration is 15–30 min. Interictal abnormalities are common and include Accelerated Long-term Forgetting (51/66), Topographical Amnesia (48/66) and Autobiographical Amnesia (58/66). Patients respond well to medications (attacks ceased in 61/66). Conclusions: This second TEA cohort supports the existence of a distinctive amnestic presentation of late-onset temporal lobe epilepsy. We are currently investigating its aetiology and the effects of anticonvulsant treatment on interictal memory disturbance.